Morphology and transport characterization of solution-processed rubrene thin films on polymer-modified substrates - Gao, Xujing (Sci Rep, 2020)
In this report, the morpho-structural peculiarities and the crystallization mechanisms in solution-processed, solvent vapor annealed (SVA) thin films of rubrene (5,6,11,12-tetraphenylnaphthacene) on different substrates were investigated. The high-quality rubrene crystal films with a triclinic crystal structure were successfully prepared on the FTO substrates (glass slide coated with fluorine-tin-oxide) modified by PLA (polylactic acid) for the first time. The area coverage of rubrene crystal and the sizes of rubrene dendritic crystals increased with increasing thickness of PLA film and concentration of rubrene solution. For rubrene molecules, FTO wafers with rough surface provided the possibility of heterogeneous nucleation. During the SVA process, there were two kinds of forces acting on the diffusion of rubrene molecules: one force was provided by the residual chloroform solvent, which was perpendicular to the substrate, and the other force was provided by gaseous dichloromethane, which was parallel to the substrate. The synergy of these two forces was proposed to explain the nucleation and the crystallization processes of rubrene films. The higher nucleus of PLA/rubrene dendrites and the layer-by-layer stacking of needle-shaped nanocrystalline PLA/rubrene were important for exploring their kinetic formation process.